Genomic basis of melanin-associated phenotypes suggests colour-specific environmental adaptations in tawny owls - Baltazar-Soares, Miguel (WILEY, 2025)
Feathers comprise a series of evolutionary innovations but also harbour colour, a key biological trait known to co-vary with life history or complex traits. Those relationships are particularly true in melanin-based pigmentation species due to known pleiotropic effects of the melanocortin pathway - originating from melanin-associated phenotypes. Here, we explore the molecular basis of melanin colouration and expected co-variation at the molecular level in the melanin-based, colour polymorphic system of the tawny owl (Strix aluco). An extensive body of literature has revealed that grey and brown tawny owl colour morphs differ in a series of life history and behavioural traits. Thus, it is plausible to expect co-variation also at molecular level between colour morphs. To investigate this possibility, we assembled the first draft genome of the species against which we mapped ddRADseq reads from 220 grey and 150 brown morphs - representing 10 years of pedigree data from a population in Southern Finland - and explored genome-wide associations with colour phenotype. Our results revealed putative molecular signatures of cold adaptation strongly associated with the grey phenotype, namely, a non-synonymous substitution in MCHR1, plus 2 substitutions in non-coding regions of FTCD and FAM135A whose genotype combinations obtained a predictive power of up to 100% (predicting grey colour). These suggest a molecular basis of cold environment adaptations predicted to be grey-morph specific. Our results potentially reveal part of the molecular machinery of melanin-associated phenotypes and provide novel insights towards understanding the functional genomics of colour polymorphism in melanin-based pigmented species.